Examining achievability of CLOs for CEFR-mapped English for academic writing course - Abdullah, Liza; Kassim, Rosnani; Anuar, Siti Zubaidah (CELPAD Research Unit, CELPAD, International Islamic University Malaysia, 2023)
The nation’s aspiration to bring the English proficiency level among Malaysian students to international standards has led to the English Language Education Reform in Malaysia and the birth of the English Language Roadmap 2015-2025. According to the Roadmap, at tertiary level, undergraduates are expected to achieve CEFR level C1 upon graduation. Thus, there is a need for Higher Learning Institutions (HLIs) to map their English Language courses’ learning outcomes to the Common European Framework of Reference for Languages (CEFR). At the Centre for Languages and Pre-University Academic Development (CELPAD), International Islamic University Malaysia (IIUM), the mapping process was done on all the English language courses and one of them was English for Academic Writing (EAW) which a university’s required course (UNICORE). After one academic session of its implementation, this study is conducted to investigate whether the Learning Outcome (LO) targeted for writing which is mapped to CEFR level C1 has been successfully attained. The LO for writing is students should be able to write clear, wellstructured exposition (cohesiveness, language, vocab) of complex subjects or topics by expanding and supporting points of view, reasons, and relevant examples. Using a qualitative research method, this study analysed 10 essays based on the marking rubric mapped against CEFR. The results revealed that the LO for writing (task, linguistic range, vocabulary range and grammatical range) targeting CEFR level C1 has been successfully achieved. These would lead to implications for any second language education programmes at large.